Outdated? The phase model of the double invasion-succession cycle in German-language gentrification research - Schütz, Moritz; Diller, Christian (ERDKUNDE, 2024)
Phase models of gentrification play a prominent role in German-language urban geography textbooks and in shaping discussions on urban gentrification. Their empiric validity however, remains a topic for debate. To contribute to this debate, we conduct a comprehensive literature review of English- and German-language gentrification research over the past 40 years, with a specific focus on phase models. We examined 4,262 papers on gentrification, employing keyword searches and forward citation to pinpoint those that reference the phase models. Out of these, 223 papers mentioned the phase models or relevant key terms, but upon closer examination, only 56 directly addressed the model, forming the basis for our qualitative content analysis. We then assess the evolution of scientific discourse on phase models and their empirical validation. Despite their widespread reference, our study reveals that only a small fraction of gentrification research explicitly engages with these models, with limited empirical evidence to support their comprehensive validity. We argue that, although these models offer a framework for understanding gentrification, they are not universally applicable and neglect important elements such as, amongst others, supply-side factors and the diversity of gentrification trajectories. We advocate for a more nuanced approach to gentrification studies, calling for empirical research that encompasses a wider array of socio-ecological factors and recognizes the heterogeneity of gentrification patterns. Furthermore, there is a need for improved integration of urban research findings into educational materials, proposing a more critical presentation of gentrification models in school textbooks to reflect their limitations and the complex realities of urban development.